2015
DOI: 10.1093/molbev/msv166
|View full text |Cite
|
Sign up to set email alerts
|

North–South Colonization Associated with Local Adaptation of the Wild Tomato SpeciesSolanum chilense

Abstract: After colonization population sizes may vary across the species range depending on environmental conditions and following colonizations. An interesting question is whether local adaptation occurs more frequently in large ancestral populations or in small derived populations. A higher number of new mutations and a lower effect of genetic drift should favor selection in large populations, whereas small derived populations may require an initial local adaptation event to facilitate the colonization of new habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
148
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(166 citation statements)
references
References 63 publications
16
148
1
1
Order By: Relevance
“…In addition, there is little to no genetic exchange between some of the southern most populations that are separated by the extremely dry Atacama desert. This leads to the conclusion that S. chilense can be divided in a northern, a central and two southern genotype groups (Böndel et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is little to no genetic exchange between some of the southern most populations that are separated by the extremely dry Atacama desert. This leads to the conclusion that S. chilense can be divided in a northern, a central and two southern genotype groups (Böndel et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…A study of the species’ demography found four genetically distinct groups; one in the north of the range, one in the central region and two in the south (one on the coast and one at high altitudes). Interestingly, the two southern groups are, even though geographically close to each other, more related to the central group than to each other, possibly due to the separating effect of the extremely arid Atacama desert (Böndel et al, 2015). In addition, S. chilense shows clear climatic adaptations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, as nucleotide diversity is higher under more persistent seed banks, recombination events are also more easily detectable in polymorphism data. The signatures of very high nucleotide diversity and high effective recombination are, for example, observed in Solanum chilense (Böndel et al ., ) and S. peruvianum (Tellier et al ., ) two outcrossing wild tomato sister species from South America with persistent seed banks. As a test for this hypothesis (Table ), I suggest that controlling for the mode of reproduction, populations (species) with more persistent seed banks should exhibit higher effective recombination rate, higher genetic diversity and smaller amount of linkage disequilibrium (LD) per locus.…”
Section: Seed Banks Affect the Effective Recombination Ratementioning
confidence: 99%
“…This rescaling effect on the coalescence of lineages in a population has also important consequences for the statistical inference of past demographic events [35]. In practice this means that the spatial structure of populations and seed bank effects on demography and selection are difficult to disentangle [5]. Nevertheless, Tellier et al [28] could use this rescaled seed bank coalescent model [19] and Approximate Bayesian Computation to infer the germination rate in two wild tomato species Solanum chilense and S. peruvianum from polymorphism data [29].…”
Section: Introductionmentioning
confidence: 99%